Deciphering the mechanism of Peptostreptococcus anaerobius-induced chemoresistance in colorectal cancer: the important roles of MDSC recruitment and EMT activation - Gu, Jinhua; Lv, Xiaojun; Li, Wenwen; Li, Guangcai; He, Xialian; Zhang, Ye; Shi, Lihong; Zhang, Xiaoqian (Frontiers in Immunology, 2023)
Peptostreptococcus anaerobius (P. anaerobius, PA) in intestinal flora of patients with colorectal cancer (CRC) are associated with poor prognosis. Studies have shown that P. anaerobius could promote colorectal carcinogenesis and progression, but whether P. anaerobius could induce chemoresistance of colorectal cancer has not been clarified. Here, both in vitro and in vivo experiments showed that P. anaerobius specifically colonized the CRC lesion and enhanced chemoresistance of colorectal cancer to oxaliplatin by recruiting myeloid-derived suppressor cells (MDSCs) into the tumor microenvironment. Furthermore, this study revealed that it was the increased secretion of IL-23 by MDSCs that subsequently facilitated the epithelial–mesenchymal transition (EMT) of tumor cells to induce chemoresistance of CRC by activating the Stat3-EMT pathway. Our results highlight that targeting P. anaerobius might be a novel therapeutic strategy to overcome chemoresistance in the treatment of CRC.